Athletes' body talk: the role of contextual body image in eating disorders as seen through the eyes of elite women athletes - De Bruin, A. P.; Oudejans, R. R. D. (Journal of Clinical Sport Psychology, 2018)
The aim of the study was to investigate if and how body image, taken from a contextual perspective, contributes to the eating disorder history. This qualitative study investigated the process of eating disorder development in eight elite women athletes in at-risk sports. The results showed that the relationship between eating disorder symptomatology and the sports environment was clearly recognized by the elite women athletes. Contextual body image, more specifically negative body-evaluations and upward body comparisons, appeared as an important factor in the development of eating disorders, particularly in the athletic context. It became clear that the two aesthetic and two endurance athletes as well as the two weight-class athletes in rowing described quite negative body evaluations in the context of sport, while some of them also recognized an impact of body image experiences in daily life. However, for both judokas, their eating disorder had nothing to do with their body image but was attributed to the weight-classes in their sport and accompanying weight making. Several unique trajectories and individual eating disorder histories were distinguished which confirms the value of taking a qualitative approach in investigating eating disorders in sport. We also discovered links between what the athletes had reported as contributors to their eating disorder history and how they told their stories by combining content analysis and narrative inquiry. Furthermore, the present study also highlights several critical aspects for prevention and treatment that should support sport federations and clinical sport psychologists in taking appropriate actions to deal more effectively with eating disorders in athletes